(untitled) (International Journal of Engineering and Computer Science, 2015)
The Medium Access Control (MAC) protocol is the main constituent which determines the system throughput using IEEE 802.11 protocol in Wireless Networks. The MAC Layer system of the IEEE 802.11 protocol is also referenced as Distributed Coordination Function (DCF). In DCF mode, source nodes contend for the use of the channel in dispersed manner via the use of the Carrier Sensing Multiple Access with Collision Avoidance (CSMA/CA) procedure. Using the CSMA/CA procedure, each source nodes sets up a Backoff time according to a randomly selected interval from zero to the Contention Window (CW) size for an extra delay time before transmitting the data packets. Binary Exponential Backoff (BEB) algorithm is used to randomize moments at which source nodes try to access the wireless medium. Additionally, in the Backoff mechanism, data packet collisions are not totally eliminated, and the system throughput is decreased when the number of source nodes is large, and there is no fairness between source nodes. The BEB algorithm occupies number of disadvantages; one vital disadvantage is the problem of fairness. This research paper analyzes the behavior of the BEB algorithm used in IEEE 802.11 protocol. We have proposed a hybrid environment using IEEE802.11p protocol to enhance the fairness of the channel access for BEB algorithm. Hybrid approach adapts the way of increase or decrease of the contention window (CW) based on the number of the frame which is delivered successfully. NS-2 simulator is used to analyze the network’s fairness of the channel access of the BEB algorithm in terms of throughput, end-to-end delay and packet dropping ratio. The result showed that comparing with IEEE 802.11 and BEB algorithm, hybrid approach with IEEE 802.11p improves the fairness of the channel access and increases the network’s throughput capacity.